Multimodel Ecologies: Cultivating Model Ecosystems in Industrial Ecology. (19th March 2015) - Bollinger, L. Andrew; Nikolić, Igor; Davis, Chris B.; Dijkema, Gerard P.J.
Summary: Many industrial ecology models may be classified as single‐use products ‐constructed to address a specific problem and of little use beyond their original context. But a knowledge ecosystem based around single‐use representations of reality wastes effort and resources and limits the impact of industrial ecology as a field. In recent years, tangible progress has been made in areas such as integrated modeling and multisimulation. However, this work tends to discount the evolutionary nature of models and their embeddedness within a changing sociotechnical environment—aspects which, we argue, are central to enabling the sustained usefulness of models in industrial ecology. We define a multimodel ecology as an interacting group of models coevolving with one another in a dynamic sociotechnical environment. A multimodel ecology perspective can facilitate model integration and reuse and highlight different ways in which models—mental, conceptual, and computational–may interact and evolve. To demonstrate the use of this perspective, we introduce and analyze an existing multimodel ecology—the Energy Modeling Laboratory. We conclude with a set of guidelines for facilitating model reuse and integration. Among others, these include use open standards, build simple components, leverage the Web, borrow proudly, and enforce sharing .